2000
DOI: 10.1103/physrevd.62.064019
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational waves from long-duration simulations of the dynamical bar instability

Abstract: Compact astrophysical objects that rotate rapidly may encounter the dynamical "bar instability." The bar-like deformation induced by this rotational instability causes the object to become a potentially strong source of gravitational radiation. We have carried out a set of long-duration simulations of the bar instability with two Eulerian hydrodynamics codes. Our results indicate that the remnant of this instability is a persistent bar-like structure that emits a long-lived gravitational radiation signal.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 50 publications
7
81
0
Order By: Relevance
“…After this time, however, the star in the 3D run begins to move away from the center of the grid, eventually making contact with the outer grid boundary. This is due to accumulated error in the linear momentum and is a well known problem associated with evolutions of stars in equatorial symmetry [66]. In our simulations, the effect can be reduced by improving spatial resolution.…”
Section: Code Tests a Unmagnetized Relativistic Starsmentioning
confidence: 80%
“…After this time, however, the star in the 3D run begins to move away from the center of the grid, eventually making contact with the outer grid boundary. This is due to accumulated error in the linear momentum and is a well known problem associated with evolutions of stars in equatorial symmetry [66]. In our simulations, the effect can be reduced by improving spatial resolution.…”
Section: Code Tests a Unmagnetized Relativistic Starsmentioning
confidence: 80%
“…Previous studies of the bar-mode instability using the m p 2 cylindrical hydrocode showed that significant motion of the system center of mass could develop at late times, resulting in a spurious signal (New et al 2000). For the simulations m p 1 reported here, we monitored the position of the overall center of mass and verified that it underwent no systematic motion during the development of the mode, in both the cym p 1 lindrical and Cartesian codes.…”
Section: Resultsmentioning
confidence: 99%
“…We examine the density in a ring of fixed and z using a complex azimuthal on the cylindrical and Cartesian hydrocodes, respectively. 0.14 For the cylindrical code, these amplitudes were calculated in the equatorial plane in a ring of width at radius D p 1/48 ; see New et al (2000) for details. For the Cartesian p 0.32 code, the amplitudes were computed on a circle of radius using a nonuniform discretization, which avoids grid p 0.32 boundaries, and a linear interpolation of density.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations